Efficacy of eDNA as an early detection indicator for Burmese pythons in the ARM Loxahatchee National Wildlife Refuge in the greater Everglades ecosystem. (July 2019) - Hunter, Margaret E.; Meigs-Friend, Gaia; Ferrante, Jason A.; Smith, Brian J.; Hart, Kristen M.
Graphical abstract: Highlights: Invasive Burmese pythons are negatively impacting the Florida Everglades ecosystem. Their cryptic nature resulted in a <1% detection rate by traditional trapping methods. Using eDNA, high python occurrence was found in a National Wildlife Refuge. The eDNA data demarcates the invaded range further to the north than previously thought. The occurrence estimates can be used for conservation and management decisions. Abstract: Environmental DNA (eDNA) detection of invasive species can be used to inform management decisions by delimiting occupied ranges and estimating detection probabilities. Environmental DNA is shed into the environment through skin cells and bodily fluids and can be detected in water samples collected from lakes, rivers, and swamps. In south Florida, USA, invasive Burmese pythons ( Python bivittatus ) occupy much of the Greater Everglades in mostly inaccessible habitat and are credited with causing severe declines in populations of native species. Detection of Burmese pythons by traditional methods, including trapping and visual searching, has been largely ineffective, making eDNA a superior method to identify invaded areas. We adapted a quantitative PCR eDNA assay for use in droplet digital PCR, a state-of-the-art method that improves the precision and accuracy of eDNA detection and quantification. From August 2014 to October 2016, locations in and around Arthur R. Marshall Loxahatchee National Wildlife Refuge in southeast Florida were surveyed for Burmese python eDNA. Positive eDNA detections were made in each of the five sampling events, assessing a total of 399 samples, with moderate-to-high occurrence ( ψ =  58–91%) and moderate detection ( p  = 38–70%) probabilities, potentially reduced by a high presence of PCR-inhibiting compounds in the water. The high occurrence rates and geographic distribution of the positive samples within Loxahatchee suggests a steady release of python eDNA from resident Burmese pythons and reduces support for transport of eDNA by boats or flowing water from the north. The first confirmed sighting of a Burmese python in the Refuge occurred in September 2016 after eDNA testing had indicated the presence of pythons. While the established population boundary is thought to be south of Loxahatchee, the eDNA detections indicate a northern range limit at, or north of, the refuge on the eastern side of the Florida peninsula. Our study demonstrates the utility of eDNA for determining more accurate range limits and expansion information for Burmese pythons, and provides a means for assessing control efforts.